Cardiac index assessment: Validation of a new non-invasive very low current thoracic bioimpedance device by thermodilution. (April 2014) - Faini, Andrea; Omboni, Stefano; Tifrea, Marius; Bubenek, Serban; Lazar, Ovidiu; Parati, Gianfranco
Abstract Introduction. The accuracy of impedance cardiography for cardiac index assessment is matter of debate, with available studies reporting inconsistent results. Our study aimed at evaluating the agreement between measurements of cardiac index provided by a new-generation thoracic electrical bioimpedance device (Hotman System) and an invasive approach based on thermodilution in humans. Methods. Cardiac index was assessed simultaneously with thoracic electrical bioimpedance and conventional thermodilution through comparison of five consecutive measurements in 51 cardiac patients, hospitalized in an intensive care unit (mean± SD age: 60 ± 11 years; 68% males). The agreement between cardiac index values measured by both methods was assessed by the Bland–Altman approach, adjusted for repeated measures. The repeatability coefficient and the intraclass correlation coefficient were used to assess reproducibility of replicates. Results. Average (± SD) cardiac index was 3.05 ± 0.91 l/min/m2 with Hotman System and 3.14 ± 1.12 l/min/m2 with thermodilution. The bias of precision was −0.09 ± 0.41. The coefficients of repeatability and intraclass correlation coefficients were high and similar for the two techniques (0.95 l/min/m2 and 0.91 for Hotman System vs 0.78 l/min/m2 and 0.90 for thermodilution). Conclusions. Cardiac index values yielded by Hotman system compares favorably with that obtained with thermodilution in cardiac patients.